Work disabilities and unmet needs for health care and rehabilitation among jobseekers: a community-level investigation using multidimensional work ability assessments - Raija Kerätär; Anja Taanila; Jari Jokelainen; Jouko Soukainen; Leena Ala-Mursula (Taylor & Francis Group, 2016)
Objective: Comprehensive understanding of the prevalence and quality of work disabilities and unmet needs for health care and rehabilitation to support return to work (RTW) among jobseekers. Design: Community-level, cross-sectional analysis with multidimensional clinical work ability assessments. Setting: Paltamo, Finland. Participants: Unemployed citizens either participating in the Full-Employment Project or long-term unemployed (n = 230, 81%). Main outcome measures: Based on data from theme interviews, patient records, supervisors' observations of work performance and clinical examinations, a physician concluded the individual's work ability, categorised into four groups: good work ability, good work ability expected after RTW support, able to transitional work only or unable to work. These groups were cross tabulated with primary diagnoses, types of plans to support RTW, as well as categories of social functioning and motivation, for which sensitivity and specificity scores in detecting work disability were calculated. Results: Only about half of the jobseekers had good work ability, 27% were found unable to work in the open labour market and 15% even eligible for a disability pension. For 20%, care or rehabilitation was seen necessary to enable RTW. Poor supervisor- and self-rated performance at work or poor social functioning appeared as sensitive measures in detecting work disability. Conclusions: Work disabilities and unmet needs for health care and rehabilitation are highly prevalent among jobseekers, as depicted using a multidimensional work ability assessment procedure inspired by the International Classification of Functioning (ICF). Further development of work ability assessment practices is clearly needed.KEY POINTS Although the association of unemployment with poor health is well known, evidence on the work ability of the unemployed remains scarce. Work disabilities are common among the unemployed. Multidimensional work ability assessment among the unemployed reveals unmet needs for care and rehabilitation to support return to work. Context sensitivity may add to the accuracy of the doctor's conclusions on work ability.